Peranan Organisasi Forum Anak Padang (FORANDANG) dalam Upaya Preventif Kekerasan Seksual pada Anak di Kota Padang - Sawitri, Wilda; Magriasti, Lince (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
The purpose of this study was to determine the role of the Padang City Children's Forum (FORANDANG) in preventing sexual violence against children in Padang City. This research uses a semi qualitative approach (quasi qualitative) with a simple research design (SRD) method. Data collection techniques using interviews and documentation studies. The results showed that FORANDANG in an effort to prevent sexual violence against children has carried out its role but not yet optimal. FORANDANG's role as a pioneer is in conducting socialisation and campaign activities. However, there are still many children who cannot distinguish between adult behaviour as a form of affection and sexual crime behaviour. While the role as a reporter, FORANDANG has never encountered a case of sexual violence that occurred in its neighbourhood, but has only reported the issue of sexual violence in vulnerable areas. There are obstacles in carrying out its role, internal obstacles such as: communication is not smooth between members, new regeneration in several sub-districts and villages that have not been carried out, limited funds and budgets, and the lack of funds. External constraints: the lack of desire of the audience to pay attention and understand what was delivered.